Canadian Hepatitis C Look-Back Investigation to Detect Transmission from an Infected General Surgeon. Issue 1 (2010) - Dawar, Meenakshi; Stuart, Tammy L; Sweet, Lamont E; Neatby, Anne M; Abbott, Lewis P; Andonov, Anton P; Wong, Tom; Gervais, Robert; Stirling, Rob
Abstract : BACKGROUND: In February 2007, a general surgeon in Charlottetown, Prince Edward Island, tested positive for hepatitis C virus (HCV). The surgeon's infection onset date could not be determined; however, episodic hepatic enzyme elevations were first detected in November 2004 and again in February 2007. HCV transmission during surgery, alhough rare, has been documented. A phased look-back HCV screening program was conducted to detect HCV transmission from this surgeon to patients who underwent the highest-risk procedures in the three years before his positive test. METHODS: Highest-risk procedures were defined as exposure-prone procedures (EPP) in which exposure to the surgeon's blood was most likely. EPP patients from January 2004 to February 2007 were identified using hospital and administrative records. Linkages with the provincial notifiable disease for HCV was performed, and death records for deceased EPP patients were reviewed. Eligible patients were invited for screening. RESULTS: Of 6248 patients seen in phase 1, 272 (4.4%) were identified to be EPP. Of the 272 patients, 248 (91.1%) were invited for HCV testing and 24 (8.8%) were deceased. To date, 231 of 248 (93.1%) patients have presented for screening. Two patients (one alive, one deceased) were HCV positive before their EPP. Viral sequence of the surgeon's isolate is unrelated to the first patient; the second individual has a resolved infection (polymerase chain reaction negative). No new transmission events were identified in the screened patients. The 95% CI of the transmission probability was estimated to be 0 to 0.016. INTERPRETATION: HCV transmission from the surgeon during a 38-month look back was unlikely. In the absence of protocols for investigating HCV transmission from infected health care workers, screening was initially prioritized to the highest-risk patients. The investigation has been satisfactorily terminated based on these results.